2014
DOI: 10.1259/bjr.20130670
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional visualization of rat brain microvasculature following permanent focal ischaemia by synchrotron radiation

Abstract: Objective: Identifying morphological changes that occur in microvessels under both normal and ischaemic conditions is crucial for understanding and treating stroke. However, conventional imaging techniques are not able to detect microvessels on a micron or sub-micron scale without angiography. In the present study, synchrotron radiation (SR)-based X-ray in-line phase contrast imaging (ILPCI) was used to acquire high-resolution and high-contrast images of rat brain tissues in both normal and ischaemic states. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…Meanwhile, the synchrotron radiation micro-computed tomography (SRμCT) imaging technique was introduced to achieve high-resolution, non-invasive 3D imaging of the complicated neurovascular networks in the rat spinal cord after injury. The synchrotron radiation light source, which is characterized by high flux density, high coherence, and monochromaticity, could obtain high-resolution imaging of the microvasculature to the submicro-level in the brain, hepatic sinusoids and rabbit eye[ 27 29 ]. Using this technique, the effect of miR-21 on the repair process of the microvascular network can be visualized in three dimensions (3D) after SCI in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the synchrotron radiation micro-computed tomography (SRμCT) imaging technique was introduced to achieve high-resolution, non-invasive 3D imaging of the complicated neurovascular networks in the rat spinal cord after injury. The synchrotron radiation light source, which is characterized by high flux density, high coherence, and monochromaticity, could obtain high-resolution imaging of the microvasculature to the submicro-level in the brain, hepatic sinusoids and rabbit eye[ 27 29 ]. Using this technique, the effect of miR-21 on the repair process of the microvascular network can be visualized in three dimensions (3D) after SCI in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no evidence exists regarding 3D alterations of neurovascular morphology in response to thoracic spinal cord compression. Synchrotron radiation microtomography (SRμCT) has been recognized as a powerful tool to explore the 3D structure of biospecimens across a large spatial range, down to submicron resolutions [20][21][22][23][24][25][26]. In a previous study, we reported the feasibility of using SRμCT to visualize and quantitatively analyze the 3D morphology of spinal cord microvasculature after acute injuries [21,24,27].…”
mentioning
confidence: 99%
“…The high intensity, high coherence, and monochromatic characteristics of SR beam light have enabled the SR-based imaging technique to obtain high-resolution images of vessel networks at micro- and even submicro-levels. In experimental studies, this method has been applied to the visualization of the 3D morphology of the microvasculature in the heart, hind limbs, tumors, and the brain 13 14 15 16 17 . However, the method’s utility for 3D visualization of the pathologic changes of angioarchitecture in trauma-induced spinal cords has not been investigated.…”
mentioning
confidence: 99%